An efficient and successful outcome after haematopoietic stem cell transplantation in a patient with an LPS-responsive beige-like anchor gene mutation - Shen, Cen; Zhang, Luying; Meng, Yan; Yang, Lu; He, Wenli; Lei, Xiaoying; Zhou, Lina; An, Yunfei; Dou, Ying (Frontiers in Pediatrics, 2024)
Lipopolysaccharide (LPS)-responsive beige ankyrin (LRBA) gene mutations were first reported as the cause of immunodeficiency syndromes and autoimmunity in 2012. The majority of LRBA patients have multiple organ system involvement and a complex clinical phenotype. Herein we present a comprehensive account on the disease progression and transplantation procedure in a patient with LRBA deficiency who exhibited progressive autoimmune disease symptoms along with recurrent pulmonary infections since the age of 6 years old. Despite receiving abatacept therapy and immunoglobulin replacement treatments to manage the symptoms, but the symptoms still progressed. Therefore, nine years after disease onset, patients were treated with allogeneic haematopoietic stem cell transplantation (allo-HSCT). The patient experienced acute and chronic graft-versus-host disease (GVHD) and recurrent infections after transplantation. During one and a half years of follow-up, we found that allogeneic haematopoietic stem cell transplantation can relieve the symptoms of autoimmune disease in patients with LRBA deficiency, and marked clinical improvement and recovery of immune function were observed following stem cell transplantation.